THE INFLUENCE OF DEMOGRAPHIC FACTORS ON IMPULSIVE CONSUMER BEHAVIOR - Urošević, Ana; Kocić, Milan; Dukić, Ana (International Journal of Economic Practice and Policy, 2024)
In modern business conditions, there is a tendency to reduce cognitive shopping, which implies shopping based on rational thinking, while at the same time, impulsive shopping is increasing. Impulsive buying is influenced by numerous factors, including demographic factors that play a significant role in shaping consumer habits and behaviour. Monitoring demographic trends and data analysis can help businesses stay abreast of changes in consumer preferences and thus adjust their marketing strategies. The purpose of this research is to examine the influence of demographic factors (gender, age, income and education) on the impulsive behavior of consumers. Empirical research was conducted using a survey on a sample of 205 respondents. The answers were analyzed using the T-test for two independent samples and the ANOVA test. There were statistically significant differences between respondents’ views on impulsive buying behavior based demographic factors, i.e., gender, age, income and education. This research indicates the importance of demographic factors for understanding impulse purchases. They can help define marketing strategies through adequate adjustment of products and promotions to respond to the needs and preferences of target demographic groups, providing personalized offers that increase sales and build brand loyalty. The paper will be helpful to marketers and researchers to comprehensively understand consumers’ impulsive behaviors.